Viajando no tempo com a história das equações do segundo grau. - ROCHA, Camila Luciana Bomfim da (Universidade Federal do Tocantins, 2023)
This paper intends to present a didactic proposal in the teaching of the equations of the second degree, having as orientation the History of Mathematics. The problematizing question is as follows: How to teach second-degree equations using the history of mathematics in the classroom? In order to answer this question, I outlined some objectives related to the construction of a didactic proposal based on information found in different works. The research was done as a form of documentary research in specific literatures, among the data of analyzes are: textbooks, paradidatic books, books of history of mathematics and articles of history of mathematics. The information extracted from these works, outlined the construction of the didactic proposal that is configured as a play entitled "Traveling in time with the history of the equations of the second degree", highlighting the main mathematicians who contributed directly to the formula for solving these equations. This proposal seeks to arouse students' interest through the historical plot and the researcher's spirit, which can provide meaningful teaching of the equations of the second degree.